Incidência de hipertensão arterial em uma capital brasileira : estudo de base populacional - Weissheimer, Fábio Liberali (2011)
The systemic arterial hypertension is a systemic condition which involves structural alterations of the artery and of the myocardium, generating continuously high levels of blood pressure. Of multifactorial causality, it is a great health issue due to its high prevalence, morbidity, mortality and costs. Brazilian researches on systemic arterial hypertension incidence are unusual. Research conducted in 2008 in Porto Alegre (RS) stated that 80% of the pre-hypertensive patients between 40 and 50 years will have systemic arterial hypertension in 10 years. Therefore, it is relevant to study the incidence of systemic arterial hypertension in Cuiabá (MT) in order to obtain technical-scientific information that subsidizes prevention policies against systemic arterial hypertension. Objective: To analyze the incidence of systemic arterial hypertension and associated factors on prehypertensive patients in Cuiabá (MT). Methods: Population-based prospective cohort approved by CEP/HUJM, with population of 400 pre-hypertensive patients watched for 6,8 years, from 2003 through 2010. Descriptive and inferential statistics were used, relative risk (Confidence Intervals - CI 95%), Pearson’s chi-square test, p<0,05 and multiple Poisson regression with robust variance. Results: Population sample of 171 patients, 61,9% men and 38,1% women, average of 46,6 years old. Follow-up time of 6,8 years. Schooling time of 9,5 years. Average per capita income of R$ 902,20. It was observed in this research that: 10,5% admit high level of salt consumption; 76,6% have daily coffee consumption; 26,9% are sedentary; 13,4% smoke cigarrettes; and 28,6% are obese. General systemic arterial hypertension incidence totaled 58,5%, from which 86% presented uncontrolled blood pressure. Stratified by exposition, the incidence of systemic arterial hypertension found was 63,8% in patients with per capita income below 2 minimum wages; 65,7% in patients that consume coffee daily; 71,7% in sedentary patients; and 77,6% in the obese. After regression, the following expositions remained associated (risk factors): obese (p<0,001), time spent watching TV higher than 4h (p< 0,000), daily coffee consumption (p< 0,005), income lower than 2 minimum wages (p< 0,041), number of inhabitants higher than 4 (p< 0,047) and age higher than 60 years old (p< 0,000). Conclusion: The research has shown that there is an 86% risk for a patient who is a resident of the urban area of Cuiabá (MT) to develop arterial hypertension in ten years, and this is associated to well known risk factors that are, in majority, modifiable. Some associations might demand a greater study. The adoption of prevention policies, treatment and control of this disease are required.